Development of a computerized inventory management system (IMS) for industry application - Ooi, Choon Kheng (2015)
Inventory Management System (IMS) are widely used in industry nowadays to increase the efficiency of item flow. The traditional method of IMS involved a lot of paper work such as spreadsheet and order list which will be more difficult to manage as the storage grew bigger. Therefore, inventory management system can be computerized to further increase the efficiency of IMS. This project aim to develop IMS software can store a large amount item data. Moreover, it has check in/out function and search function that run using scan QR Code. Besides that, the software also has the feature of low stock warning function to warn the user if the item has low quantity. To develop the software, first the criteria of the software are determined followed by choosing the software development tools to develop the software that can achieve the criteria of the software. Next the software will be developed and debugged. This paper focuses on developing IMS software for SMEs and biomedical field company usage.